How to Draw Manga Myths & Legends In Simple Steps - Li, Yishan (Search Press(UK), 2017)
28 easy-to-follow step-by-step illustrations to get you drawing these colourful manga creatures from myths and legends
Drawing
1
Keywords: Caricatures and cartoons -- Technique; Caricatures and cartoons -- Japan -- Technique